(untitled) (SAARC Journal of Agriculture, 2018)
The experiment was conducted to compare the effect of Moringa oleifera leaf extract with synthetic antioxidant on beef meatball. Five types of beef meatballs were formulated for this purpose. Meatballs were made with control (0%), 0.1% Beta Hydroxyl Anisole (BHA), 0.1, 0.2 and 0.3% Maringa oleifera leaf extract, respectively. Quality and safety evaluation of meatballs were determined by sensory, physiochemical, biochemical and microbiological tests. After preparation meatballs were preserved at -20˚C. The analyses were conducted at 0, 15t, 30 and 60 days of interval. An ANOVA of a 5x4 factorial experiment in completely randomized design having three replications per treatment was used for the analyses of data. Considering CP, tenderness, juiciness, overall acceptability, cooking loss, FFA, POV and TBARS value it can be concluded that Moringa oleifera leaf extract up to a level of 0.3% may replace BHA for meatball preservation without deteriorating its quality. In case of sensory evaluation 0.2% Moringa leaf extract shows better results. But on the basis of nutrient quality, physicochemical properties, biochemical analysis and microbial analysis 0.3% Moringa leaf extract group is more satisfactory than other treatment groups. SAARC J. Agri., 16(1): 23-34 (2018)